Analysis Study about Facts of Tax Evasion and Smuggling in Syria & Its Consequences on the Development - عكروش محمد; زهيري علاء الدين (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Advanced as well as third world countries are facing the trouble of tax evasion and smuggling, which has small large scales. In the fact this trouble is so large that it negatively affects the resources, economic performance and society moral principles. This is why the trouble of tax evasion and smuggling should be included by the economic reform program. A good reform needs the following conditions: To find out and expose the problem so as to make it difficult for smuggling and tax evasion to continue. Statistical scientific identification of the fact of tax evasion and smuggling, its characters, methods, volumes and amounts. The tax evasion volume in Syria has reached around (200 bln). SP This means that the state efforts and attentions to get back those capitals for the purpose of replacement and investment, which leads to public prosperity and development, this is because the phenomenon has a great relation with economic security and development as well as with others social and economic fields.